DkHsfB2a/b-mediated regulatory network in high CO2 induced persimmon fruit deastringency - Rong Jin; Wei Wu; Xiao-fen Liu; Kun-song Chen; Xue-ren Yin (Postharvest Biology and Technology, 2026)

Microalgae-based bioremediation of reverse osmosis concentrate (ROC): Mechanisms, techno-economic bottlenecks, and circular bioeconomy perspectives - Na-Hui Hao; Jun Li; Ya-Rong Qi; Zhuo Chen; Yu-Ming Wang; Yu-Jia Gao; Xu-Cheng Cai; Yu Hong; Hong-Ying Hu; Yin-Hu Wu (Desalination, 2026)

Synergistic modulation of nickel–manganese glycerate via sequential sulfurization and oxidation for high-performance battery–supercapacitor hybrids - Tsung-Rong Kuo; Lu-Yin Lin; Tzu-Han Chou; You-Zher Yu; Chutima Kongvarhodom; Sibidou Yougbaré; Muhammad Saukani; Hung-Ming Chen (Journal of Environmental Chemical Engineering, 2026)

PepOSX-AI: CPP - an interpretable transformer-based deep learning model for prediction of cell-penetrating peptides - Haowen Chen; Weiwei He; Kaiyan Feng; Rong Xu; Sheng Yin; Lin Zheng; Jing Chen; Mouming Zhao; Jucai Xu; Lijun You (Analytica Chimica Acta, 2026)

Engineering bimetallic Cobalt–Iron glycerate Co-Catalysts on bismuth vanadate for improved charge transfer and photoelectrochemical catalytic water oxidation - Tsung-Rong Kuo; He-Jin Li; Kai-Jie Chuang; Chutima Kongvarhodom; Sibidou Yougbaré; Muhammad Saukani; Hung-Ming Chen; Lu-Yin Lin (Fuel, 2026)

Heavy silicon isotope and mass-independent mercury isotope fractionation signals of Archean TTGs: Insights into the recycling of the silicified oceanic crust in the source region - Xiao Hu; Wenbin Zhu; Haizhen Wei; Runsheng Yin; Yongxiang Li; Yiwei Rong; Di Chen (Chemical Geology, 2026)

Assessing cognitive impairment in epilepsy using Arterial spin-labeled (ASL) perfusion imaging - Qiuyan Chen; Jie Zhang; Rong Chen; Yameng Qin; Xu Wang; Qiang Liu; Zheng Yin; Ping Yang; Feng Rao; Longnan Wang; Mengyun Li; Yanzi Jin; et al. (Brain Imaging and Behavior, 2026)

Oxygen mass transfer characteristics of different hollow-fiber bubble-free aeration membranes via clean water oxygenation tests under different aeration and measurement modes - Zhe Yuan; Chun-Hai Wei; Jing-Su Liu; Zhi-Wei Lian; Jing-Yin Wang; Hua-Rong Yu; Hong-Wei Rong; Zhi-Hui Pan; Zhong-Lin Nie; Ya-Song Chen; Xia Huang (Water Research, 2026)

Natural pyrite-enhanced co-culture system for simultaneous nitrate and ammonium removal under low C/N conditions: Mechanistic insights and real wastewater application - Kuang-di Xu; Pan He; Xiang-lin Liu; Lei Yu; Si-jia Li; Quan Wang; Rong-ping Chen; Ke Yin; Guang Guo; Wen-Jie Xu; Gong-De Wu (Bioresource Technology, 2026)

Multidimensional effects of personalized exercise intervention in type 2 diabetes: a randomized controlled trial - Dan Liu; Di Cheng; Qinyi Wang; Ying Zhang; Piao Kang; Chufan Zhao; Hongfeng Mao; Jing Qu; Sheng Liu; Xiaojing Gao; Rui Han; Jingyi Guo; et al. (Science Bulletin, 2026)

Microenvironment-driven interactions between mobile genetic elements and defense systems modulate the plastisphere resistome - Rong Xia; Jose Luis Balcazar; Jingqiu Liao; Xiaole Yin; Hong Chen; Pedro J.J. Alvarez; Pingfeng Yu (Water Research, 2026)

Copper recovery from the smelting products of copper electroplating sludge by roasting and slurry electrolysis - Jinchuan Qin; Rong Wang; Yin Huang; Qian Liang; Jiancheng Shu; Mengjun Chen (Waste Management, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Genome-wide Identification and Expression Analysis of the ABF Gene Family in Achnatherum splendens - Shan Yin; Mingsu Chen; Ming Hu; XiaoYing Li; Jingru Wang; Jiahuan Niu; Zhangqi Song; Huan Yang; Hongbing Li; Rong Li (Plant Molecular Biology Reporter, 2026)

Influence of winter-fallow management strategies on the stability of soil organic matter in a typical rice paddy region of southwestern China - Meihui Tian; Sihua Zhu; Bin Liu; Jitao Lv; Shanyi Tian; Rong Huang; Xiaohong Zuo; Meichun Duan; Yongguang Yin; Tao Jiang; Dingyong Wang; Xinping Chen (Agriculture, Ecosystems & Environment, 2026)

Evaluation of near infrared spectroscopy for direct detection of common microplastics contamination in camel Milk powder - Chunxu WAN; Yin LIU; Jing XIE; Feng CHEN; Huijie SHEN; Rong LI (Food Chemistry, 2026)

Efficacy and Safety of Temozolomide for the Treatment of Advanced or Recurrent Ependymoma: A Meta-Analysis - Rong Zhang; Binyan Liu; Zhuang Kang; Shenglan Li; Yingfan Sun; Jiachen Wang; Xin Yang; Shuo Yin; Feng Chen; Wenbin Li (Journal of Pharmaceutical Innovation, 2026)

Pyrite-driven redox modulation improves microbial tolerance to furan inhibitors in hydrogen production from lignocellulosic hydrolysates - Hao-Yu Sun; Xin Xu; Si-Jia Li; Lei Yu; Quan Wang; Rong-Ping Chen; Ke Yin; Guang Guo; Xu Sun; Yu-ting Xin; Wen-jie Xu; Gong-De Wu (Bioresource Technology, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Plant-soil feedback driven by root-associated fungal communities accelerates the secondary succession of bare saline-alkaline grassland patches - Xiaona Zheng; Yuhong Yin; Dan Yang; Jingjuan Bi; Wenlong He; Siya Li; Xiao Liang; Jigui Chen; Rong Wang; Zhiying Guo; Xing Li; Tao Zhang; et al. (Plant and Soil, 2026)

Production of neofemales by 17β-estradiol and YY super-male breeding in northern snakehead (Channa argus) - Mi Ou; Yang Zhang; Rong Huang; Yaping Wang; Jianxiong Yin; Qing Luo; Kunci Chen; Haiyang Liu; Xincheng Zhang; Shuzhan Fei; Yuandong Sun; Baixiang Chen; et al. (Aquaculture, 2026)

Effects of biochar on humification in Cu-rich pig manure composting under continuous high temperature: Microbial mechanisms - Xuehan Liu; Mengtong Li; Xiaochang Wang; Yanan Yin; Rong Chen (Process Safety and Environmental Protection, 2026)

Tailoring nickel glycerate electrodes through precursor chemistry and sulfurization for enhanced battery-supercapacitor hybrid performance - Tsung-Rong Kuo; Yun-Hsi Wang; Bo-Yang Chuang; Chutima Kongvarhodom; Sibidou Yougbaré; Muhammad Saukani; Hung-Ming Chen; Lu-Yin Lin (Journal of Environmental Chemical Engineering, 2025)

A peptidomics-based investigation of the synergistic effects of neutral and Alcalase proteases on release of antioxidant peptides from soybean protein isolates - Shulong Cai; Liqi Fan; Dan Liu; Changxing Wei; Na Yang; Xichao Fu; Rong Tang; Jucai Xu; Sheng Yin; Xin Chen (Food Chemistry, 2025)

Freshwater flux-induced salinity effect on ENSO in the tropical Pacific under global warming - Hai Zhi; Jiahao Chen; Rong-Hua Zhang; Minmin Wu; Jiaxiang Gao; Lu-Ying Yin (Climate Dynamics, 2025)

New aromatic butenolides from the plant endophytic fungus Malbranchea umbrina D16 - Xian-An Chen; Han-Zhuang Weng; Lei-Ming Wu; Shu-Qi Wu; Rong Pu; Tao Yuan; Sheng Yin; Gui-Hua Tang (Natural Product Research, 2025)

Discovery and profiling of efficient microbial strains for struvite biomineralization in high-salinity wastewater - Bing-bing Liu; Rong-ji Zhao; Nimaichand Salam; Shu-hong Xu; Rong Shi; Jiang-hao Zhu; Zi-qing Chen; Cheng-yin Liu; Bing Li; Wen-Jun Li (Antonie van Leeuwenhoek, 2025)

Estimating daily NOx and CO2 emissions in typical megacities of east China using TROPOMI NO2 observations - Yizhen Jia; Minghui Tao; Hongming Zhang; Pengfei Ma; Bin Zhao; Rong Li; Dejia Yin; Lijuan Zhang; Haijun Huang; Lunche Wang; Yi Wang; Liangfu Chen (Atmospheric Environment, 2025)

Efficacy and safety of an mRNA encoding neutralizing antibody against SARS-CoV-2 in non-human primates - Hang Chi; Suo-Qun Zhao; Yun-Peng Liu; Xiao-Chuan Xiong; Xia Zhong; Xing-Xing Suo; Xing-Yao Huang; Can Yue; Jing-Jing Zhang; Zhe Cong; Na Li; Fei-Xue Du; et al. (Science Bulletin, 2025)

Removal of aqueous As(Ⅴ) by biochar stabilized green synthesized iron nanoparticles: Optimization, mechanism and DFT insights - Xueping Li; Hong Chen; Kun Rong; Qi Gao; Jianchao Jin; Shilai Yi; Qian Yang; Chunlong Sun; Ruimin Li; Zhenjiang Yin; Zaiwang Zhang (Journal of Environmental Chemical Engineering, 2025)

Surface engineering of copper peroxide nanodots and Au nanozyme on porphyrin-based metal-organic frameworks induces cascade reactions for colorectal cancer treatment - Haoyu Chen; Rong Liu; Jiaxin Fu; Xiaohan Zhang; Xiaohua Zhu; Mingjie Wei; Feng Liu; Peng Yin; Haitao Li; Youyu Zhang; Meiling Liu; Juewen Liu (Chemical Engineering Journal, 2025)

Early Temporal Dynamics of Gonadal Development and Sexually Dimorphic Gene Expression During Sex Differentiation in Mandarin Fish (Siniperca chuatsi) - Yi Rong; Yuanyuan Wang; Jinzhi Zhao; Lei Chen; Kuangxin Chen; Binbin Tao; Yanlong Song; Jianxiong Yin; Kewei Zeng; Wen Song; Wei Hu; Ji Chen (Marine Biotechnology, 2025)

IFN-γ2 enhances proliferation and differentiation of muscle cells: a novel target of natural grass feeding mode improving muscle quality in grass carp (Ctenopharyngodon idella) - Huijie Chen; Yin Wang; Jieya Liu; Qiushi Yang; Jiamin Lu; Tingting Xu; Rong Tang; Dapeng Li (Fish Physiology and Biochemistry, 2025)

The prognostic significance of histopathological growth patterns in liver metastases undergoing surgery: a systematic review and meta-analysis - Xiang-Yu Wang; Bo Zhang; Yin-Chen Gu; Mei Yang; Bao-Rui Tao; Rong-Quan Sun; Yi-Tong Li; Zhen-Mei Chen; Sen-Feng Ying; Chen-He Yi; Yan Geng; Rui Zhang; et al. (Clinical & Experimental Metastasis, 2025)

Plasmon-enhanced fluorescence sensor based on Au nanocages for sensitive detection of norepinephrine - Chenye Xu; Shilin Chen; Wen Sun; Rong Xu; Xiangyuan Yin; Dongsheng Guo; Yaqiong Yang (Analytica Chimica Acta, 2025)

Wind Direction and Strength Determine the Genetic Structure of an Insect‐Pollinated Plant Across Heterogeneous Landscape - Jun‐Yin Deng; Rong‐Hua Fu; Stephen G. Compton; Chuan Yuan; Matthew M. Kling; Xiao‐Yong Chen; Yao‐Bin Song; Kai Jiang; Mei Liu; Jaco M. Greeff; Yan Chen (Journal of Biogeography, 2025)
Aim Dispersal of plant propagules and their genes is crucial for plant responses to landscape heterogeneities, yet the mechanisms behind this dispersal remain unclear. Ficus species depend on wind‐borne fig wasps for pollination, but research on airflow effects on Ficus genetic structure has produced conflicting results. Our study aims to clarify the role of wind in shaping the genetic structure of such plants with wind‐borne insect pollinators by examining how geomorphological complexity interacts with air movements to influence genetic structures. Location Southwest China: Sichuan, Yunnan, Guangxi and Guizhou provinces. Taxon Ficus tikoua Bur., Ficus , Moraceae. Methods We sampled 56 F. tikoua sites across southwest China, characterised by high geomorphologic complexity. River basins and predominant winds were visualised across the sampled regions. Wind connectivity between sampled sites during the main pollination season was modelled based on hourly daily wind data. The maternal and biparental genetic structure of sites were reconstructed using chloroplast DNA (cpDNA) and nuclear SSR (nuSSR) markers. Links between genetic structure, location, and wind parameters were estimated by Mantel or partial Mantel tests. Results The plant's maternal genetic structure was defined by river systems, with two distinct cpDNA groups located in the Yangtze and Pearl River basins, respectively. The boundaries for nuclear variation were less clearly delimited geographically. Sites with mixtures of nuSSR groups were concentrated where prevailing winds arrived from several directions. Stronger between‐site air flows increased nuSSR geneflow and genetic similarities, while populations receiving more wind flow were also more genetically variable. Main Conclusions Our study reveals how plant gene dispersal reflects air and water movements that in turn respond to geomorphologic complexity, thereby directly demonstrating the effects of wind on gene flow of plants with wind‐borne insect pollinators. Wind data matching pollinator flight times and large sample sizes are crucial for testing wind effects.

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Reduced mixed Ni-Co-Al metal oxide catalysts with rich oxygen vacancy derived from layered double hydrotalcite for selective hydrogenation of furfuryl alcohol to 1,5-Pentanediol - Nan Xi; Qiwang Li; Yi Chen; Ruixi Bao; Qinglian Wang; Yixiong Lin; Jun Yue; Rong Wang; Chen Yang; Wang Yin; Ting Qiu (Chemical Engineering Journal, 2025)

Drivers and spatial distribution of soil organic carbon and total nitrogen in China’s drylands - Shihang Zhang; Yusen Chen; Bo Zhu; Yongxing Lu; Hao Guo; Xing Guo; Ye Tao; Jing Zhang; Xiaoying Rong; Benfeng Yin; Yongxin Zang; Xiaobing Zhou; et al. (CATENA, 2025)

Identification of Potential Causal Genes for Neurodegenerative Diseases by Mitochondria-Related Genome-Wide Mendelian Randomization - Kang-Fu Yin; Ting Chen; Xiao-Jing Gu; Zheng Jiang; Wei-Ming Su; Qing-Qing Duan; Xiang-Jin Wen; Bei Cao; Ju-Rong Li; Li-Yi Chi; Yong-Ping Chen (Molecular Neurobiology, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Comparison of molecular testing methods for diagnosing non-tuberculous mycobacterial infections - Leilei Wang; Yu Chen; Qingqing Wang; Jue Pan; Rong Bao; Wenting Jin; Yumeng Yao; Tingting Fang; Na Li; Sichun Luan; Xiaoyu Yin; Le Qin; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Pollution status and assessment of seven heavy metals in the seawater and sediments of Hangzhou Bay, China - Rong Zhu; Yan-Yan Zeng; Li-Min Liu; Lu Yin; Kai-Ping Xu; Wei-Feng Chen; Shang-Chun Li; Xiao-Feng Zhou (Marine Pollution Bulletin, 2024)

Modulating the Pronociceptive Effect of Sleep Deprivation: A Possible Role for Cholinergic Neurons in the Medial Habenula - Xiang-Sha Yin; Bai-Rong Chen; Xi-Chun Ye; Yun Wang (Neuroscience Bulletin, 2024)

Integrated transcriptome and metabolomic analyses uncover the mechanism of cadmium-caused mouse spermatogonia apoptosis via inducing endoplasmic reticulum stress - Jie Wu; Qizi Yin; Yi Wang; Rong Wang; Wenjing Gong; Yihang Chen; Mingming Zhang; Yehao Liu; Yanli Ji (Reproductive Toxicology, 2024)

Mitigating nitrite inhibition in Klebsiella strain denitrification: Stimulating endogenous driving force with microscale zero-valent iron - Wen-ying Cao; Kuang-di Xu; Su Zhang; Si-jia Li; Yi-cheng Yuan; Jing-xuan Lu; Lei Yu; Shao-hua Zhou; Jun-ting Gan; Quan Wang; Rong-ping Chen; Ke Yin (Chemical Engineering Journal, 2024)

Synergistic metabolism intervention and immune activation for antitumor therapy by biomineralized lactate oxidase - Yuxuan Ge; Zixin Wang; Yujia Lu; Fan Rong; Bin Hao; Zhao Li; Junsheng Chen; Yin Wang (Chemical Engineering Journal, 2024)

Incorporation of atomic Fe-oxide triggers a quantum leap in the CO2 methanation performance of Ni-hydroxide - Amisha Beniwal; Dinesh Bhalothia; Yin-Rong Chen; Jui-Cheng Kao; Che Yan; Nozomu Hiraoka; Hirofumi Ishii; Mingxing Cheng; Yu-Chieh Lo; Xin Tu; Yun-Wei Chiang; Chun-Hong Kuo; et al. (Chemical Engineering Journal, 2024)

Catalytic hydrotreatment of fast pyrolysis liquids from Pine wood using Ru-based catalysts supported on nitrogen-doped carbon materials - Yunhui Xia; Nan Xi; Xinyang Yu; Maohua Luo; Shi Chen; Qinglian Wang; Yixiong Lin; Rong Wang; Hao Li; Jun Yue; Chen Yang; Wang Yin; et al. (Fuel, 2024)

Fluoride exposure during puberty induces testicular impairment via ER stress-triggered apoptosis in mice - Rong Wang; Wenjing Gong; Yumeng Jiang; Qizi Yin; Ziyue Wang; Jie Wu; Mingming Zhang; Mengyuan Li; Yehao Liu; Juan Wang; Yuanhua Chen; Yanli Ji (Food and Chemical Toxicology, 2024)

NCOA4-mediated ferritinophagy participates in cadmium-triggered ferroptosis in spermatogonia - Didi Jia; Mingming Zhang; Mengyuan Li; Wenjing Gong; Wei Huang; Rong Wang; Yihang Chen; Qizi Yin; Jie Wu; Zhongxiu Jin; Juan Wang; Yehao Liu; et al. (Toxicology, 2024)

Fibroblast-localized lncRNA CFIRL promotes cardiac fibrosis and dysfunction in dilated cardiomyopathy - Shuai Yuan; Xudong Zhang; Jiabing Zhan; Rong Xie; Jiahui Fan; Beibei Dai; Yanru Zhao; Zhongwei Yin; Qian Liu; Dao Wen Wang; Huaping Li; Chen Chen (Science China Life Sciences, 2024)

Advances in understanding bioaerosol release characteristics and potential hazards during aerobic composting - Sai Yang; Yanan Yin; Wenrong Zhang; Haichao Li; Xiaochang Wang; Rong Chen (Science of The Total Environment, 2024)

Myosin heavy chain isoform expression and meat quality characteristics of different muscles in yak (Bos grunniens) - Xueyuan Bai; Feng Yin; Ang Ru; Ming Li; Wei Tian; Guiyan Zhang; Qingwen Chen; Rong Chai; Yanxia Liu; Wenming Cui; Hongmei Shi; Chaozhi Zhu; et al. (Meat Science, 2024)

Biochar improves the humification process during pig manure composting: Insights into roles of the bacterial community and metabolic functions - Yanan Yin; Xiaohui Tao; Yifei Du; Mengtong Li; Sai Yang; Wenrong Zhang; Chao Yang; Haichao Li; Xiaochang Wang; Rong Chen (Journal of Environmental Management, 2024)

Damming-associated landscape change benefits a wind-dispersed pioneer plant species - Hang Ji; Yong-Rong He; Hong-Yue Li; Ling Lu; Jia-Hui Li; Jie Zou; Rong Wang; Jun-Yin Deng; Xiao-Yong Chen (New Forests, 2024)

Calcium ions induced ι-carrageenan-based gel-coating deposited on zein nanoparticles for encapsulating the curcumin - Qingyuan Ge; Shuang Rong; Chenxi Yin; David Julian McClements; Qi Fu; Qi Li; Yahong Han; Fuguo Liu; Suqing Wang; Shuai Chen (Food Chemistry, 2024)

Relationships between different types of biochar and N2O emissions during composting based on roles of nosZ-carrying denitrifying bacterial communities enriched on compost and biochar particles - Yanan Yin; Mengjin Gu; Wenrong Zhang; Chao Yang; Haichao Li; Xiaochang Wang; Rong Chen (Bioresource Technology, 2024)

Nrf2 suppresses erastin-induced ferroptosis through activating system Xc(-) in ovarian cancer - Yongkang Li; Rong Yin; Miao Liang; Cheng Chen (Molecular & Cellular Toxicology, 2024)

The benefit of omeprazole exposure on all-cause mortality and length of ICU/hospital stay might vary with age in critically ill pediatric patients: A cohort study - Fang-Fang Jiang; Yu Guo; Zheng Zhang; Sun-Jun Yin; Yu-Xin Fan; Yan-Hua Huang; Ya-Jia Li; Li-Rong Chen; Kai Qian; Gong-Hao He (European Journal of Clinical Pharmacology, 2024)

Association of residential greenness with chronotype among children - Yiting Chen; Yabin Hu; Rong Li; Wenhui Kang; Anda Zhao; Ruoyu Lu; Yong Yin; Shilu Tong; Jiajun Yuan; Shenghui Li (Science of The Total Environment, 2023)

An airflow-driven system for scalable production of nano-microfiber wrapped triboelectric yarns for wearable applications - Yu Chen; Jie Hua; Yali Ling; Yang Liu; Mingtai Chen; Beomjun Ju; Wei Gao; Amanda Mills; Xiaoming Tao; Rong Yin (Chemical Engineering Journal, 2023)

Species diversity and related ecology of chiggers on small mammals in a unique geographical area of Yunnan Province, southwest China - Yu Guo; Juan-Xiu Zhou; Xian-Guo Guo; Wen-Yu Song; Cheng-Fu Zhao; Zhi-Wei Zhang; Rong Fan; Ting Chen; Yan Lv; Peng-Wu Yin; Dao-Chao Jin (Experimental and Applied Acarology, 2023)

Improved efficiency of Sedum lineare (Crassulaceae) in remediation of arsenic-contaminated soil by phosphate-dissolving strain P-1 in association with phosphate rock - Shaohui Yang; Rong Yin; Chen Wang; Jiehua Wang (Environmental Geochemistry and Health, 2023)

Structure-diversified terpenoids from Salvia prattii and their protective activity against alcoholic liver diseases - Xiu-wen Yin; Xiang-xiang Bian; Yan-fang Chen; Ming Zhang; Lan Wu; Fu-cai Ren; Fu-rong Yang; Xiang-dong Pu; Bing-yuan Yang; Chuan-pu Shen (Phytochemistry, 2023)

Concentrations and homologue patterns of SCCPs and MCCPs in the serum of the general population of adults in Hangzhou, China - Jianyun Zhang; Hanyu Liao; Yanhong Chen; Xue Li; Rong Chen; Shufen Han; Shuren Liu; Shanshan Yin (Chemosphere, 2023)

Microbial community and antibiotic resistance gene distribution in food waste, anaerobic digestate, and paddy soil - Xin-rong Pan; Seyit Yuzuak; Jia-min Lou; Lei Chen; Yin Lu; Jian-e Zuo (Science of The Total Environment, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Effect of slaughter age and postmortem aging time on tenderness and water-holding capacity of yak (Bos grunniens) longissimus thoracis muscle - Xueyuan Bai; Feng Yin; Ang Ru; Wei Tian; Qingwen Chen; Rong Chai; Yanxia Liu; Wenming Cui; Jiahui Li; Mancai Yin; Chaozhi Zhu; Gaiming Zhao (Meat Science, 2023)

Individual and joint association of phenols, parabens, and phthalates with childhood lung function: Exploring the mediating role of peripheral immune responses - Yiting Chen; Jinhong Wu; Rong Li; Wenhui Kang; Anda Zhao; Yong Yin; Shilu Tong; Jiajun Yuan; Shenghui Li (Journal of Hazardous Materials, 2023)

Characteristics and comparisons of the aerobic and anaerobic denitrification of a Klebsiella oxytoca strain: Performance, electron transfer pathway, and mechanism - Cheng-jia Ju; Shareen Niyazi; Wen-yin Cao; Quan Wang; Rong-ping Chen; Lei Yu (Journal of Environmental Management, 2023)

HucMSC-EVs Facilitate In Vitro Development of Maternally Aged Preantral Follicles and Oocytes - Ying-Yi Zhang; Weijie Yang; Yi Zhang; Zhanhong Hu; Yingyan Chen; Yerong Ma; Anran Yang; Zhan Shi; Hanjing Zhou; Peipei Ren; Libing Shi; Jiamin Jin; et al. (Stem Cell Reviews and Reports, 2023)
Follicle developmental capacity and oocyte quality decline with advanced maternal age. Extracellular vesicles from human umbilical cord mesenchymal stem cells (HucMSC-EVs) act as a potential therapeutic product in the treatment of age-related ovarian dysfunction. In vitro culture (IVC) of preantral follicles is a useful method for understanding the mechanism of follicle development and is a promising means for improving female fertility. However, whether HucMSC-EVs have beneficial effects on aged follicle development during IVC has not yet been reported. Our research demonstrated that follicular development with single-addition withdrawal of HucMSC-EVs was better than that with continuous treatment with HucMSC-EVs. HucMSC-EVs facilitated the survival and growth of follicles, promoted the proliferation of granulosa cells (GCs), and improved the steroid hormone secretion of GCs during IVC of aged follicles. Both GCs and oocytes could uptake HucMSC-EVs. Moreover, we observed elevated cellular transcription in GCs and oocytes after treatment with HucMSC-EVs. The RNA sequencing (RNA-seq) results further validated that the differentially expressed genes are related to the promotion of GC proliferation, cell communication, and oocyte spindle organization. Additionally, the aged oocytes displayed a higher maturation rate, presented less aberrant spindle morphology, and expressed a higher level of the antioxidant protein Sirtuin 1 (SIRT1) after treatment with HucMSC-EVs. Our findings suggested that HucMSC-EVs can improve the growth and quality of aged follicles and oocytes in vitro through the regulation of gene transcription, which provides evidence for HucMSC-EVs as potential therapeutic reagents to restore female fertility with advanced age. Graphical Abstract

Microbial diversity and functional profiling in coastal tidal flat sediment with pollution of nutrients and potentially toxic elements - Yihong Yue; Huanan Rong; Zhihong Yang; Xueyang Pan; Yin Chen; Ming Yang (Journal of Soils and Sediments, 2023)

Independent and combined associations of multiple-heavy-metal exposure with lung function: a population-based study in US children - Yiting Chen; Anda Zhao; Rong Li; Wenhui Kang; Jinhong Wu; Yong Yin; Shilu Tong; Shenghui Li; Jianyu Chen (Environmental Geochemistry and Health, 2023)

The city-wide full-scale interactive application of sewage surveillance programme for assisting real-time COVID-19 pandemic control – A case study in Hong Kong - Wai-yin Ng; Wai Thoe; Rong Yang; Wai-ping Cheung; Che-kong Chen; King-ho To; Kan-ming Pak; Hon-wan Leung; Wai-kwan Lai; Tsz-kin Wong; Tat-kwong Lau; Ka-wing Au; et al. (Science of The Total Environment, 2023)

Responses of Bacillus sp. under Cu(II) stress in relation to extracellular polymeric substances and functional gene expression level - Ling-ling Wang; Zheng-yan Yin; Yun Xu; Miao-yu Deng; Kai-ming Zhang; Quan Wang; Rong-ping Chen; Lei Yu (Environmental Science and Pollution Research, 2023)

Zinc efficiently extracted from zinc calcine by reduced wet grinding: ZnFe2O4 to ZnO and Fe3O4 - Shaoqin Chen; Xiangfei Zeng; Qian Liang; Ling Hu; Shuyuan Chen; Dejun He; Yunhui Han; Zhisheng Zhao; Rong Huang; Yin Huang; Songshan Zhou; Jiqin Wang; et al. (Journal of Cleaner Production, 2023)

Biochar enhanced organic matter transformation during pig manure composting: Roles of the cellulase activity and fungal community - Yanan Yin; Mengtong Li; Xiaohui Tao; Chao Yang; Wenrong Zhang; Haichao Li; Yucong Zheng; Xiaochang Wang; Rong Chen (Journal of Environmental Management, 2023)

Preliminary Investigation on Marine Radar Oil Spill Monitoring Method Using YOLO Model - Bo Li; Jin Xu; Xinxiang Pan; Rong Chen; Long Ma; Jianchuan Yin; Zhiqiang Liao; Lilin Chu; Zhiqiang Zhao; Jingjing Lian; Haixia Wang (Journal of Marine Science and Engineering, 2023)
Due to the recent rapid growth of ocean oil development and transportation, the offshore oil spill risk accident probability has increased unevenly. The marine oil spill poses a great threat to the development of coastal cities. Therefore, effective and reliable technologies must be used to monitor oil spills to minimize disaster losses. Based on YOLO deep learning network, an automatic oil spill detection method was proposed. The experimental data preprocessing operations include noise reduction, gray adjustment, and local contrast enhancement. Then, real and synthetically generated marine radar oil spill images were used to make slice samples for training the model in the YOLOv5 network. The detection model can identify the effective oil spill monitoring region. Finally, an adaptive threshold was applied to extract the oil slicks in the effective oil spill monitoring regions. The YOLOv5 detection model generated had the advantage of high efficiency compared with existing methods. The offshore oil spill detection method proposed can support real-time and effective data for routine patrol inspection and accident emergency response.

Field detection of small pests through stochastic gradient descent with genetic algorithm - Yin Ye; Qiangqiang Huang; Yi Rong; Xiaohan Yu; Weiji Liang; Yaxiong Chen; Shengwu Xiong (Computers and Electronics in Agriculture, 2023)

Biochar reduces bioavailability of phosphorus during swine manure composting: Roles of phoD-harboring bacterial community - Yanan Yin; Chao Yang; Mengtong Li; Sai Yang; Xiaohui Tao; Yucong Zheng; Xiaochang Wang; Rong Chen (Science of The Total Environment, 2023)

Zero-valent iron boosts nitrate-to-ammonia bioconversion via extracellular electron donation and reduction pathway complementation - Xue Li; Jie Li; Xiao-Rong Yu; Yong-Kun Zhu; Hou-Qi Liu; Lin Chen; Jing Wu; Xian-Zhong Fu; Shuo Cui; Tian-Yin Huang; Ru-Quan Ye; Wen-Wei Li (Resources, Conservation and Recycling, 2023)

Exposure–response relationship between temperature, relative humidity, and varicella: a multicity study in South China - Yihan Li; Jialing Li; Zhihua Zhu; Weilin Zeng; Qi Zhu; Zuhua Rong; Jianxiong Hu; Xing Li; Guanhao He; Jianguo Zhao; Lihua Yin; Yi Quan; et al. (Environmental Science and Pollution Research, 2023)

Genetic characteristics of human coronavirus HKU1 in mainland China during 2018 - Xiangpeng Chen; Yun Zhu; Qi Li; Gen Lu; Changchong Li; Rong Jin; Lei Li; Baoping Xu; Liwei Gao; Ju Yin; Zhengde Xie (Archives of Virology, 2022)

Sequencing and comparative analysis of chloroplast genomes of three medicinal plants: Gentiana manshurica, G. scabra and G. triflora - Rong Zhao; Shuyue Yin; Jianing Xue; Chang Liu; Yanping Xing; Haibo Yin; Xue Ren; Jixiang Chen; Dingding Jia (Physiology and Molecular Biology of Plants, 2022)

Source–sink dynamics assists the maintenance of a pollinating wasp - Xin Tong; Yuan‐Yuan Ding; Jun‐Yin Deng; Rong Wang; Xiao‐Yong Chen (Molecular Ecology, 2021)
Dispersal that unites spatially subdivided populations into a metapopulation with source–sink dynamics is crucial for species persistence in fragmented landscapes. Understanding such dynamics for pollinators is particularly urgent owing to the ongoing global pollination crisis. Here, we investigated the population structure and source–sink dynamics of a pollinating wasp ( Wiebesia sp. 3) of Ficus pumila in the Zhoushan Archipelago of China. We found significant asymmetry in the pairwise migrant numbers for 22 of 28 cases on the historical timescale, but only two on the contemporary timescale. Despite a small population size, the sole island not colonized by a superior competitor wasp ( Wiebesia sp. 1) consistently behaved as a net exporter of migrants, supplying large sinks. Comparable levels of genetic diversity, with few private alleles and low genetic differentiation (total F st : 0.03; pairwise F st : 0.0005–0.0791), were revealed among all the islands. There was a significant isolation‐by‐distance pattern caused mainly by migration between the competition‐free island and other islands, otherwise the pattern was negligible. The clustering analysis failed to detect multiple gene pools for the whole region. Thus, the sinks were most probably organized into a patchy population. Moreover, the estimates of effective population sizes were comparable between the two timescales. Thus the source–sink dynamics embedded within a well‐connected population network may allow Wiebesia sp. 3 to persist at a competitive disadvantage. This study provides evidence that metapopulations in the real world may be complicated and changeable over time, highlighting the necessity to study such metapopulations in detail.

Seamount age prediction machine learning model based on multiple geophysical observables: methods and applications in the Pacific Ocean - Yongliang Bai; Yilin Rong; Jihong Sun; Leiming Chen; Diya Zhang; Zhengtong Yin (Marine Geophysical Research, 2021)

Comparative Transcriptomic Analyses of Haemophilus parasuis Reveal Differently Expressed Genes among Strains with Different Virulence Degrees - Yuan Y. Zhou; Chao Wang; Jing Yuan; Rong L. Yin; Xin Chen; Rui Li; Xue L. Zhang; Jing Wang; Chen Huang; Rong H. Yin (Current Microbiology, 2021)

Identification of Ala2Thr mutation in insulin gene from a Chinese MODY10 family - Juan Zhang; Yanjun Liu; Ming Li; Xiaoxu Ge; Ying Wang; Xin Huang; Di Yang; Rong Zhang; Yating Chen; Ming Lu; Jun Yin; Mingqiang Song; et al. (Molecular and Cellular Biochemistry, 2020)

Chinese public participation monitoring and warning system for geological hazards - Sheng-nan Wu; Yu Lei; Peng Cui; Rong Chen; Pi-hua Yin (Journal of Mountain Science, 2020)

Sky islands as foci for divergence of fig trees and their pollinators in southwest China - Jun‐Yin Deng; Rong‐Hua Fu; Stephen G. Compton; Mei Liu; Qin Wang; Chuan Yuan; Lu‐Shui Zhang; Yan Chen (Molecular Ecology, 2020)
The dynamics of populations and their divergence over time have shaped current levels of biodiversity and in the case of the “sky islands” of mountainous southwest (SW) China have resulted in an area of exceptional botanical diversity. Ficus tikoua is a prostrate fig tree subendemic to the area that displays unique intraspecific diversity, producing figs typical of different pollination modes in different parts of its range. By combining climate models, genetic variation in populations of the tree's obligate fig wasp pollinators and distributions of the different plant phenotypes, we examined how this unusual situation may have developed. We identified three genetically distinct groups of a single Ceratosolen pollinator species that have largely parapatric distributions. The complex topography of the region contributed to genetic divergence among the pollinators by facilitating geographical isolation and providing refugia. Migration along elevations in response to climate oscillations further enhanced genetic differentiation of the three pollinator groups. Their distributions loosely correspond to the distributions of the functionally significant morphological differences in the male figs of their host plants, but postglacial expansion of one group has not been matched by spread of its associated plant phenotype, possibly due to a major river barrier. The results highlight how interplay between the complex topography of the “sky island” complex and climate change has shaped intraspecies differentiation and relationships between the plant and its pollinator. Similar processes may explain the exceptional botanical diversity of SW China.

First report of isolation and complete genome of Vibrio rotiferianus strain SSVR1601 from cage‐cultured black rockfish ( Sebastes schlegelii ) associated with skin ulcer - Zheng Zhang; Yong‐xiang Yu; Yong Jiang; Yin‐geng Wang; Mei‐jie Liao; Xiao‐jun Rong; Kai Wang; Hao Zhang; Jing Chen (Journal of Fish Diseases, 2019)
Vibrio rotiferianus is an important marine pathogen of various aquatic organisms and can be found widely distributed in the marine environment. To further characterize this pathogen, the pathogenic properties and genome of V. rotiferianus SSVR1601 isolated from Sebastes schlegelii with skin ulcer were analysed. SSVR1601 was shown to be short rod‐shaped cell with a single polar flagellum. Different degrees of pathological changes in fish kidney, intestine, gills and liver were observed after SSVR1601 challenge. The SSVR1601 genome consists of two chromosomes and two plasmids with a total of 5,717,113 bp, 42.04%–44.93% GC content, 5,269 predicted CDSs, 134 tRNAs and 40 rRNAs. The common virulence factors including OMPs, haemolysin, flagellin, DNase, entF , algU , tcpI , acfB and rfaD were found in strain SSVR1601. Furthermore, factors responsible for iron uptake ( fur , fepC and ccmC ) and types II, IV and VI secretion systems were detected, which are likely responsible for the pathogenicity of SSVR1601. The antimicrobial resistance genes, bacA , tet34 and norM, were detected based on Antibiotic Resistance Genes Database. The phylogenetic analysis revealed SSVR1601 to be most closely related to V. rotiferianus strains CAIM577 and B64D1.

Smectite formation in metalliferous sediments near the East Pacific Rise at 13°N - Kunbo Rong; Zhigang Zeng; Xuebo Yin; Shuai Chen; Xiaoyuan Wang; Haiyan Qi; Yao Ma (Acta Oceanologica Sinica, 2018)

Ionizing Radiation Blocks Hair Cell Regeneration in Zebrafish Lateral Line Neuromasts by Preventing Wnt Signaling - Rong Li; Guixiang Liao; Guo Yin; Baiyao Wang; Miaohong Yan; Xiaoshan Lin; Wenqing Zhang; Xiaohui Chen; Shasha Du; Yawei Yuan (Molecular Neurobiology, 2018)

CDK inhibitor SU9516 induces tetraploid blastocyst formation from parthenogenetically activated porcine embryos - Qing Guo; Long Jin; Hai-Ying Zhu; Xiao-Chen Li; Yu-Chen Zhang; Xiao-Xu Xing; Guang-Lei Zhang; Mei-Fu Xuan; Qi-Rong Luo; Zhao-Bo Luo; Jun-Xia Wang; Jin-Dan Kang; et al. (Biotechnology Letters, 2017)

RepSox improves viability and regulates gene expression in rhesus monkey–pig interspecies cloned embryos - Hai-Ying Zhu; Long Jin; Qing Guo; Zhao-Bo Luo; Xiao-Chen Li; Yu-Chen Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Guang-Lei Zhang; Qi-Rong Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

The developmental competence of oocytes parthenogenetically activated by an electric pulse and anisomycin treatment - Yu-Chen Zhang; Long Jin; Hai-Ying Zhu; Qing Guo; Xiao-Chen Li; Guang-Lei Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Qi-Rong Luo; Zhao-Bo Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

Repeated pre-training sleep restriction in adolescent rats impaired spatial performance - Su-Rong Yang; Huan-Xin Sun; Zhen-Zhen Hu; Si-Heng Wang; Hui Sun; Yin-Jia Xue; Chen-Bo Ye (Sleep and Biological Rhythms, 2017)

PCI-24781 can improve in vitro and in vivo developmental capacity of pig somatic cell nuclear transfer embryos - Long Jin; Hai-Ying Zhu; Qing Guo; Xiao-Chen Li; Yu-Chen Zhang; Guang-Lei Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Qi-Rong Luo; Xi-Jun Yin; Jin-Dan Kang (Biotechnology Letters, 2016)

Evaluation of the major royal jelly proteins as an alternative to fetal bovine serum in culturing human cell lines - Di Chen; Xiao-xuan Xin; Hao-cheng Qian; Zhang-yin Yu; Li-rong Shen (Journal of Zhejiang University-SCIENCE B, 2016)

Improving the antioxidant activity and enriching salvianolic acids by the fermentation of Salvia miltiorrhizae with Geomyces luteus - Yun Xing; Le Cai; Tian-peng Yin; Yang Chen; Jing Yu; Ya-rong Wang; Zhong-tao Ding (Journal of Zhejiang University-SCIENCE B, 2016)

Isolation and characterization of 13 polymorphic microsatellite loci for the fig wasp, Ceratosolen sp. (Hymenoptera: Agaonidae) - Lu Tan; Jun-Yin Deng; Rong-Hua Fu; Yan Chen (Applied Entomology and Zoology, 2016)

Genetic Diversity and Population Structure Patterns in Chinese Cherry (Prunus pseudocerasus Lindl) Landraces - Tao Chen; Xiao-jiao Huang; Jing Zhang; Qing Chen; Yin Liu; Hao-ru Tang; Dong-ming Pan; Xiao-rong Wang (Plant Molecular Biology Reporter, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

A novel acetylcholinesterase inhibitor and calcium channel blocker SCR-1693 improves Aβ25–35-impaired mouse cognitive function - Zhengping Zhang; Rong Chen; Wenji An; Chunmei Wang; Gaoyong Liao; Xiaoliang Dong; Aijing Bi; Zhimin Yin; Lan Luo (Psychopharmacology, 2016)

Pantoea pleuroti sp. nov., Isolated from the Fruiting Bodies of Pleurotus eryngii - Yuanwei Ma; Yonggang Yin; Chengbo Rong; Sanfeng Chen; Yu Liu; Shouxian Wang; Feng Xu (Current Microbiology, 2016)

High precision in-situ Pb isotopic analysis of sulfide minerals by femtosecond laser ablation multi-collector inductively coupled plasma mass spectrometry - HongLin Yuan; Cong Yin; Xu Liu; KaiYun Chen; ZhiAn Bao; ChunLei Zong; MenNing Dai; ShaoCong Lai; Rong Wang; ShaoYong Jiang (Science China Earth Sciences, 2015)

Modified method for estimating organic carbon density in discontinuous Karst soil using ground-penetrating radar and geostatistics - Lei Li; Yin-hang Xia; Shu-juan Liu; Wei Zhang; Xiang-bi Chen; Hua Zheng; Hu-sen Qiu; Xun-yang He; Yi-rong Su (Journal of Mountain Science, 2015)

Abundance and distribution of fatty acids in sediments of the South Mid-Atlantic Ridge - Xin Huang; Zhigang Zeng; Shuai Chen; Xuebo Yin; Xiaoyuan Wang; Yao Ma; Baoju Yang; Kunbo Rong; Yunchao Shu; Tao Jiang (Journal of Ocean University of China, 2015)

Component characteristics of polycyclic aromatic compounds in sediments of the South Mid-Atlantic Ridge - Xin Huang; Zhigang Zeng; Shuai Chen; Xuebo Yin; Xiaoyuan Wang; Yao Ma; Baoju Yang; Kunbo Rong; Yunchao Shu; Tao Jiang (Acta Oceanologica Sinica, 2014)

Determination of 16 phthalate esters in tea samples using a modified QuEChERS sample preparation method combined with GC-MS/MS - Peng Yin; Xin Liu; Hongping Chen; Rong Pan; Guicen Ma (Food Additives & Contaminants: Part A, 2014)

Overexpression of S100P promotes colorectal cancer metastasis and decreases chemosensitivity to 5-FU in vitro - Lei Dong; Fule Wang; Xiaona Yin; Ling Chen; Gang Li; Feiyan Lin; Wuhua Ni; Jianbo Wu; Rong Jin; Lei Jiang (Molecular and Cellular Biochemistry, 2014)

Estrogen receptor α gene PvuII polymorphism and coronary artery disease: a meta-analysis of 21 studies - Jie Ding; Hui Xu; Xiang Yin; Fu-rong Zhang; Xiao-ping Pan; Yi-an Gu; Jun-zhu Chen; Xiao-gang Guo (Journal of Zhejiang University-SCIENCE B, 2014)

Isolation an Aldehyde Dehydrogenase Gene from Metagenomics Based on Semi-nest Touch-Down PCR - Rong Chen; Chenglu Li; Xiaolin Pei; Qiuyan Wang; Xiaopu Yin; Tian Xie (Indian Journal of Microbiology, 2014)

Charlson comorbidity index helps predict the risk of mortality for patients with type 2 diabetic nephropathy - You-Qun Huang; Rong Gou; Yong-Shu Diao; Qing-Hua Yin; Wen-Xing Fan; Ya-Ping Liang; Yi Chen; Min Wu; Li Zang; Ling Li; Jing Zang; Lu Cheng; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

Perceptual quality assessment of SAR image compression - Anzhou Hu; Rong Zhang; Dong Yin; Yuan Chen; Xin Zhan (International Journal of Remote Sensing, 2013)

Component characteristics of organic matter in hydrothermal barnacle shells from Southwest Indian Ridge - Xin Huang; Zhigang Zeng; Shuai Chen; Xuebo Yin; Xiaoyuan Wang; Huijing Zhao; Baoju Yang; Kunbo Rong; Yao Ma (Acta Oceanologica Sinica, 2013)

A Highly Selective Turn-On Fluorescent Chemosensor for Zinc Ion in Aqueous Media - Zeng-chen Liu; Zheng-yin Yang; Yan-xia Li; Bao-dui Wang; Yong Li; Tian-rong Li; Yong-jie Ding (Journal of Fluorescence, 2013)

Addition of Co2+ to culture medium decides the functional expression of a recombinant nitrile hydratase in Escherichia coli - Xiaolin Pei; Qiuyan Wang; Chenglu Li; Xiaopu Yin; Rong Chen; Tian Xie (Biotechnology Letters, 2013)

Expression of ethylene response genes during persimmon fruit astringency removal - Xue-ren Yin; Yan-na Shi; Ting Min; Zheng-rong Luo; Yun-cong Yao; Qian Xu; Ian Ferguson; Kun-song Chen (Planta, 2012)

Glypican-3, a novel prognostic marker of hepatocellular cancer, is related with postoperative metastasis and recurrence in hepatocellular cancer patients - Su Ning; Chen Bin; Huang Na; Shen Peng; Ding Yi; Ye Xiang-hua; Zeng Fang-yin; Zheng Da-yong; Luo Rong-cheng (Molecular Biology Reports, 2012)

Erratum to: Olfactory responses of Neoseiulus cucumeris (Acari: Phytoseiidae) to odors of host plants and Frankliniella occidentalis (Thysanoptera: Thripidae)–plant complexes - Feng Zhong; Yu-Rong He; Yan Gao; Guo-Jun Qi; Chen-Yin Zhao; Li-Hua Lu (Arthropod-Plant Interactions, 2011)

Olfactory responses of Neoseiulus cucumeris (Acari: Phytoseiidae) to odors of host plants and Frankliniella occidentalis (Thysanoptera: Thripidae)–plant complexes - Feng Zhong; Yu-Rong He; Yan Gao; Guo-Jun Qi; Chen-Yin Zhao; Li-Hua Lu (Arthropod-Plant Interactions, 2011)

Analysis of variable sites between two complete South China tiger (Panthera tigris amoyensis) mitochondrial genomes - Wenping Zhang; Bisong Yue; Xiaofang Wang; Xiuyue Zhang; Zhong Xie; Nonglin Liu; Wenyuan Fu; Yaohua Yuan; Daqing Chen; Danghua Fu; Bo Zhao; Yuzhong Yin; et al. (Molecular Biology Reports, 2011)

Monitoring of flow field based on stable isotope geochemical characteristics in deep groundwater - Lu-wang Chen; He-rong Gui; Xiao-xi Yin (Environmental Monitoring and Assessment, 2011)

Malignant transformation of 293 cells induced by ectopic expression of human Nanog - Yan-Li Lin; Zheng-Bin Han; Fu-Yin Xiong; Li-Yuan Tian; Xiao-Jie Wu; Shi-Wei Xue; Yan-Rong Zhou; Ji-Xian Deng; Hong-Xing Chen (Molecular and Cellular Biochemistry, 2011)

Synthesis, Characterization, DNA Binding Properties and Antioxidant Activity of Ln(III) Complexes with Schiff Base Ligand Derived from 3-Carbaldehyde Chromone and Aminophenazone - Yong Li; Zheng-yin Yang; Tian-rong Li; Zeng-chen Liu; Bao-dui Wang (Journal of Fluorescence, 2011)

Bacillus beringensis sp. nov., a psychrotolerant bacterium isolated from the Bering Sea - Yong Yu; Hui-Rong Li; Yin-Xin Zeng; Bo Chen (Antonie van Leeuwenhoek, 2011)

TRANSPARENT TESTA 12 genes from Brassica napus and parental species: cloning, evolution, and differential involvement in yellow seed trait - You-Rong Chai; Bo Lei; Hua-Lei Huang; Jia-Na Li; Jia-Ming Yin; Zhang-Lin Tang; Rui Wang; Li Chen (Molecular Genetics and Genomics, 2009)

Hydrogenation of ortho-nitrochlorobenzene on activated carbon supported platinum catalysts - Cheng-jun Jiang; Hong Yin; Zhi-rong Chen (Journal of Zhejiang University-SCIENCE B, 2005)